Treatment of Hepatitis C in Two Paediatric Patients using Sofosbuvir during Haematopoietic Stem Cell Transplantation. Issue 8 (November 2019) - Grasso, Antonio G; Sonzogni, Aurelio; Zanon, Davide; Maestro, Alessandra; Loiacono, Stefano; Maximova, Natalia
We report the first two paediatric cases of sofosbuvir treatment during high-intensity myeloablative conditioning and engraftment phases of haematopoietic stem cell transplantation. These reports highlight the safety of sofosbuvir during all phases of transplantation and the lack of interaction between sofosbuvir and alkylating or immunosuppressive agents.